Role of PCNA and RFC in promoting Mus81-complex activity - Sisakova, Alexandra; Altmannova, Veronika; Sebesta, Marek; Krejci, Lumir (BMC biology, 2017)
BACKGROUND: Proper DNA replication is essential for faithful transmission of the genome. However, replication stress has serious impact on the integrity of the cell, leading to stalling or collapse of replication forks, and has been determined as a driving force of carcinogenesis. Mus81-Mms4 complex is a structure-specific endonuclease previously shown to be involved in processing of aberrant replication intermediates and promotes POLD3-dependent DNA synthesis via break-induced replication. However, how replication components might be involved in this process is not known. RESULTS: Herein, we show the interaction and robust stimulation of Mus81-Mms4 nuclease activity by heteropentameric replication factor C (RFC) complex, the processivity factor of replicative DNA polymerases that is responsible for loading of proliferating cell nuclear antigen (PCNA) during DNA replication and repair. This stimulation is enhanced by RFC-dependent ATP hydrolysis and by PCNA loading on the DNA. Moreover, this stimulation is not specific to Rfc1, the largest of subunit of this complex, thus indicating that alternative clamp loaders may also play a role in the stimulation. We also observed a targeting of Mus81 by RFC to the nick-containing DNA substrate and we provide further evidence that indicates cooperation between Mus81 and the RFC complex in the repair of DNA lesions generated by various DNA-damaging agents. CONCLUSIONS: Identification of new interacting partners and modulators of Mus81-Mms4 nuclease, RFC, and PCNA imply the cooperation of these factors in resolution of stalled replication forks and branched DNA structures emanating from the restarted replication forks under conditions of replication stress.
Keywords: "flap" endonukleasy; proliferační antigen buněčného jádra; Saccharomyces cerevisiae Proteins; replikační protein C; Endonucleases; Saccharomyces cerevisiae; Recombination; Replication factor C; DNA vazebné proteiny; Replication; endonukleasy; Proliferating cell nuclear antigen; Recombination, Genetic; Flap Endonucleases; Saccharomyces cerevisiae - proteiny; rekombinace genetická; replikace DNA; Mus81 complex; DNA Replication; Proliferating Cell Nuclear Antigen; DNA-Binding Proteins; Replication Protein C